Experiences of nurses with the use of personal protective equipment in a COVID-19 emergency department - Liliana Figueiredo; Olivério Ribeiro; Eduardo Santos (Instituto Politécnico de Viseu, 2021)
Introduction: The 2019 Coronavirus disease pandemic (COVID-19) has rapidly evolved and affected healthcare workers, who have been required to wear personal protective equipment (PPE) to reduce the risk of acquiring or transmitting Coronavirus disease. PPE has been a challenge to patient care, interpersonal relationships and the health and well-being of professionals. Objetives: To describe the nurses' experiences with the use of personal protective equipment in a COVID-19 emergency service. Methods: A hermeneutic phenomenological qualitative methodology was applied, which allowed for a reflection on the basic structures of the lived experiences reported by the participants. 11 nurses were interviewed in a hospital in northern Portugal. Results: From the analysis of the interviews, four themes emerged regarding the nurses' experiences and, in relation to the theme under study, several categories were identified: difficulties and obstacles, implications for use, duration of use, and attitudes of users and relatives. Within these categories, several subcategories were identified and carefully analysed in this study. Conclusion: The study evidenced several adverse effects and limitations arising from the use of PPE, suggesting the development of policies and strategies to ensure the well-being of nurses and better performance capacity in performing procedures and providing care.